Copper-surface-mediated synthesis of acetylenic carbon-rich nanofibers for active metal-free photocathodes - Zhang, Tao; Hou, Yang; Dzhagan, Volodymyr; Liao, Zhongquan; Chai, Guoliang; Loeffler, Markus; Olianas, Davide; Milani, Alberto; Xu, Shunqi; Tommasini, Matteo; Zahn, Dietrich R. T.; Zheng, Zhikun; et al. (Nature Communications, 2018)
The engineering of acetylenic carbon-rich nanostructures has great potential in many applications, such as nanoelectronics, chemical sensors, energy storage, and conversion, etc. Here we show the synthesis of acetylenic carbon-rich nanofibers via copper-surface-mediated Glaser polycondensation of 1,3,5-triethynylbenzene on a variety of conducting (e.g., copper, graphite, fluorine-doped tin oxide, and titanium) and non-conducting (e.g., Kapton, glass, and silicon dioxide) substrates. The obtained nanofibers (with optical bandgap of 2.51 eV) exhibit photocatalytic activity in photoelectrochemical cells, yielding saturated cathodic photocurrent of ca. 10 μA cm-2 (0.3-0 V vs. reversible hydrogen electrode). By incorporating thieno[3,2-b]thiophene units into the nanofibers, a redshift (ca. 100 nm) of light absorption edge and twofold of the photocurrent are achieved, rivalling those of state-of-the-art metal-free photocathodes (e.g., graphitic carbon nitride of 0.1-1 μA cm-2). This work highlights the promise of utilizing acetylenic carbon-rich materials as efficient and sustainable photocathodes for water reduction.
CRIS-Team Scopus Importer:2023-03-20